2020
DOI: 10.2147/cia.s242038
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pharmacological Therapy of Osteoporosis: What’s New?</p>

Abstract: Osteoporosis and fragility fractures are relevant health issues because of their impact in terms of morbidity, mortality, and socioeconomic burden. Despite this alarming scenario, both underdiagnosis and undertreatment are common features of osteoporotic patients, particularly those who have already sustained a fragility fracture. Pharmacotherapy of osteoporosis is the main treatment option for these patients because of strong evidence about the efficacy of available drugs targeting bone metabolism. However, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 41 publications
0
70
0
1
Order By: Relevance
“…Some studies revealed also the changing trends: till 2010 [ 12 ] or 2003 [ 14 ], the increase was established and afterwards the decreasing trend was observed. However, one should be aware that fragility fractures are underestimated and undertreated, although pharmacological treatment demonstrated to be effective for reducing their incidence, particularly in secondary prevention care [ 18 ]. Recently, the hip fracture incidence during COVID-19 pandemic was described and the number of hip fractures did not change in comparison with earlier periods [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed also the changing trends: till 2010 [ 12 ] or 2003 [ 14 ], the increase was established and afterwards the decreasing trend was observed. However, one should be aware that fragility fractures are underestimated and undertreated, although pharmacological treatment demonstrated to be effective for reducing their incidence, particularly in secondary prevention care [ 18 ]. Recently, the hip fracture incidence during COVID-19 pandemic was described and the number of hip fractures did not change in comparison with earlier periods [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is considered one of the main health problems in developed countries, considering the high morbidity and mortality of fragility fractures and the resulting economic burden [ 18 ]. The proximal femur is one of the most affected sites by fragility fractures [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Romosozumab, an Scl-Ab agent, has completed phase III studies. Romosozumab was found to be able to reduce the threat of vertebral, hip, and other fractures in postmenopausal women suffering from osteoporosis [ 69 , 70 ]. Many studies suggest that Scl-Ab has promising prospects in the treatment of periodontitis.…”
Section: The Altered Secretory Function Of Osteocytes In Periodontitimentioning
confidence: 99%